The hyperpolarization-activated cyclic nucleotide-gated 4 channel as a potential anti-seizure drug target - Kharouf, Qays; Phillips, A. Marie; Bleakley, Lauren E.; Morrisroe, Emma; Oyrer, Julia; Jia, Linghan; Ludwig, Andreas; Jin, Liang; Nicolazzo, Joseph A.; Cerbai, Elisabetta; Romanelli, M. Novella; Petrou, Steven; et al. (British Journal of Pharmacology, 2020)
Background and Purpose Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are encoded by four genes (HCN1-4) with distinct biophysical properties and functions within the brain. HCN4 channels activate slowly at robust hyperpolarizing potentials, making them more likely to be engaged during hyperexcitable neuronal network activity seen during seizures. HCN4 channels are also highly expressed in thalamic nuclei, a brain region implicated in seizure generalization. Here, we assessed the utility of targeting the HCN4 channel as an anti-seizure strategy using pharmacological and genetic approaches. Experimental Approach The impact of reducing HCN4 channel function on seizure susceptibility and neuronal network excitability was studied using an HCN4 channel preferring blocker (EC18) and a conditional brain specific HCN4 knockout mouse model. Key Results EC18 (10 mg center dot kg(-1)) and brain-specific HCN4 channel knockout reduced seizure susceptibility and proconvulsant-mediated cortical spiking recorded using electrocorticography, with minimal effects on other mouse behaviours. EC18 (10 mu M) decreased neuronal network bursting in mouse cortical cultures. Importantly, EC18 was not protective against proconvulsant-mediated seizures in the conditional HCN4 channel knockout mouse and did not reduce bursting behaviour in AAV-HCN4 shRNA infected mouse cortical cultures. Conclusions and Implications These data suggest the HCN4 channel as a potential pharmacologically relevant target for anti-seizure drugs that is likely to have a low side-effect liability in the CNS.
CRIS-Team WoS Importer:2020-06-30